Elliptically symmetric Bessel distribution: the distribution of XY - Nadarajah, Saralees; Gupta, Arjun K. (Tamkang Journal of Mathematics, 2006)
The exact distribution of the product XY is derived when (X, Y) has the elliptically symmetric Bessel distribution.